Building a healthy migrant workforce in Singapore - A cross-sectional study to understand health-seeking behaviours of male migrant workers - Nurul Amanina Binte Hussain; Sheena Ramazanu; Priscilla Ang; Halina Talib; Si Ying Tan; Hui Xiang Chia; Sharon Tan; Jeremy Fung Yen Lim; Jason CH Yap (Elsevier, 2024)
Background: The healthcare policies for migrant workers in Singapore had a traditional focus on improving occupational health and preventing workplace injuries. The COVID-19 pandemic led to a rapid paradigm shift in the provision of healthcare for migrant workers, with an urgent focus on improving the accessibility and affordability of primary and preventive health services and strengthening public health surveillance. The purpose of this study is to identify areas for improvement, so that policy makers can improve the implementation effectiveness of healthcare policies for migrant workers. This is achieved by establishing a baseline understanding of (a) the health-seeking behaviours of migrant workers in Singapore, (b) how they consume primary and preventive health services, and (c) systemic gaps in the delivery of services. Methods: A cross-sectional study was conducted at five migrant worker dormitories and two community spaces in Singapore, between August and November 2022. 1101 male migrant workers participated in a survey and 1089 valid responses were analysed. Multivariable logistic regression was used to identify sociodemographic factors associated with health service utilisation and awareness of the new healthcare financing plan introduced for migrant workers, called the Primary Care Plan (PCP). Results: The mean age of participants was 34 years. Most of them were of Indian or Bangladeshi nationality. At least 82 % of participants reported that they could access varying health services in Singapore and 73 % were satisfied with the costs of healthcare. However, a lower percentage of the participants (54 %) had seen a doctor, mostly for respiratory, fever or musculoskeletal conditions, and only 7 % saw a dentist at least once in a year. This was attributable to their low perceived need to see a doctor (91 %) or dentist (71 %). While the prevalence of chronic diseases (4 %) was low among the participants, about one-third of participants smoked (26 %), consumed alcohol (32 %), or resorted to self-treatment or medication (39 %). Conclusion: This study corroborated with previous observational studies where migrant workers in Singapore only sought care during an acute episode of illness. While participants perceived healthcare in Singapore to be accessible and affordable, there was limited evidence to suggest that preventive health care was prioritised. This indicates possible gaps in current outreach programmes and further development of new targeted programmes to increase the health literacy and awareness of primary and preventive health services among migrant workers in Singapore.